Is the international frog legs trade a potential vector for deadly amphibian pathogens?. Issue 8 (19th November 2009) - Gratwicke, Brian; Evans, Matthew J; Jenkins, Peter T; Kusrini, Mirza D; Moore, Robin D; Sevin, Jennifer; Wildt, David E
Abstract : There have been surprisingly few analyses of how the international trade in amphibians for food affects the conservation status of this group. We analyzed information from the UN Commodity Trade Statistics Database and found that, by volume, Indonesia supplied nearly half of the animals entering the world's US40 million per year international frog legs trade, and that – collectively – France, Belgium, and the US imported more than 75% of all frog legs traded internationally. Nonetheless, a close examination of available information from 1996 through 2006 revealed that most countries throughout the world participated in the frog legs trade at some level. These extensive international amphibian trade networks could facilitate the spread of pathogens, includingBatrachochytrium dendrobatidis, which has been identified as a threat connected with the disappearance and possible extinction of over 90 amphibian species around the world. Given the size and extent of the international trade in frog legs, we advocate for the rigorous implementation of clear policies regulating the domestic and international movement of amphibians for food.